A hidden cost of mucus production by phytoplankton: Viscosity hinders nutrient uptake. Issue 3 (4th February 2022) - Inman, Bryce G.
Abstract: Diverse phytoplankton exude polysaccharides that can form a viscous mucus layer surrounding their cells, facilitating complex chemical exchanges with bacteria. An unexplored ramification of mucus production is the influence of its viscosity on the diffusion of nutrients such as vitamins to the cell. Here, I use simulations to demonstrate that mucus viscosity increases the nutrient concentration gradient but always reduces the flux to the cell. Uptake is marginally improved during nutrient pulses, as the mucus acts like a sponge by retaining nutrients near the cell. Lower uptake in the presence of mucus presents a fitness cost that any ecological benefits of mucus must outweigh. I derive a relationship between mucus viscosity and nutrient uptake that can be used to test hypotheses of mutualistic interactions between phytoplankton and bacteria. This work emphasizes the need for empirical measurements of macronutrient diffusion through mucus layers and provides a framework for interpreting those results.